ANALISIS PENJADWALAN PROYEK KLINIK SPESIALIS MATA & THT AYANI DENGAN PERT & CPM - FAIZAL ADDIN ACHMAD; YONAS PRIMA ARGA RUMBYARSO (CV KULTURA DIGITAL MEDIA, 2024)
Clinics are one of the health facilities that are important for people's lives, for this reason the provision of health facilities is a priority scale where the construction of the Ayani Eye & ENT Specialist Clinic building in Pontianak City, West Kalimantan is one of them. Project scheduling is one of the elements of planning results, which can provide information about the planned schedule, project progress, & project delays, these things can affect the quality & quantity of work if correct implementation is not anticipated, both in terms of implementation methods, coordination between the owner and the contractor. . In this research, Time Scheduling analysis was carried out using PERT (Project Evaluation and Review Technique) & CPM (Critical Path Method) on the Ayani eye & ENT specialist clinic building project to determine the critical path and determine the probability that project work can be completed on time. Based on the analysis carried out, the critical path obtained is with the following details, A-B-C-D-E-H-Y-P-AG-AK-AN-AM-AO with a duration of 189 which is obtained from the results of calculations using the CPM method and probability using PERT calculations, namely that it can be completed in 189 with a percentage of 62% of the completion targets that have been made